Analgesic Efficacy of Dexmedetomidine as Adjuvant to Levo-Bupivacine in Ultrasound Guided Erector Spinae Plan Block for Modified Radical Mastectomy - Mohamed, Sahar Abdel-Baky; Mohamed, Mohamed Farouk; Mohamed, Montaser Abdelfataah; Edward, Peter Rafaat; El-Rahman, Ahmed Mohammed Abd (International Journal of Membrane Science and Technology, 2023)
Background& aim: There are several advantages to properly managing post-masctetomy pain. With single shot interfascial plane blocks, local anesthetic adjuvants enhance analgesia duration. They improve the analgesic impact of local anesthetics. Dexamethasone, magnesium sulphate and dexmedetomidine, are examples of adjuvants with diverse modes of action. This research examined the analgesic effects of dexmedetomidine in women who had undergone a modified radical mastectomy (MRM). Methods and Patients: The research included forty women with histopathologically confirmed breast cancer. They were all scheduled for MRM and were randomly assigned to one of two groups: those who got levobupivacaine alone (group C) or those who received dexmedetomidine plus levobupivacaine (group D) during ultrasound (US)-guided erector spinae plane block (ESPB). The two groups were compared in terms of their hemodynamics, demographics, time until the first request for analgesia, numeric rating scale (NRS) scores, Richmond Agitation & Sedation scale (RASS) scores and total opioid use. Results: There were no statistically significant differences observed between the two groups in terms of baseline data. The set of participants referred to as group D had a statistically significant reduction in heart rate on many instances. Furthermore, it was discovered that group D had a substantial reduction in postoperative NRS ratings and a heightened degree of recovery from sedation, as shown by the RASS. Furthermore, it was noted that group D had a significantly reduced overall analgesic dose (9.12±0.46 vs. 6.24±1.37 mg; p= 0.02) and a prolonged duration until first analgesia (6.21±1.28 vs. 7.13±1.79 hours; p< 0.001). Conclusion: The use of dexmedetomidine in combination with levobupivacaine ESPB has been shown to enhance postoperative analgesia compared to the use of levobupivacaine alone. This improvement in postoperative analgesia leads to enhanced comfort levels for patients. Further research is necessary to corroborate these results via future studies conducted in several places.